Economic Burden and Quality of Life of Hepatocellular Carcinoma in Greater China: A Systematic Review - Zou, Huimin; Li, Meng; Lei, Qing; Luo, Zejun; Xue, Yan; Yao, Dongning; Lai, Yunfeng; Ung, Carolina Oi Lam; Hu, Hao (Frontiers in Public Health, 2022)
Background Hepatocellular carcinoma (HCC) accounts for more than 85%-90% of primary liver cancer globally, and approximately 45% of deaths from HCC occur in greater China. This disease poses a significant economic burden for patients, payers and society and significantly affects patients' quality of life (QoL). However, such impact of HCC in greater China has not been well characterized. This review was conducted to analyze the current evidence about the economic and humanistic impact of HCC in greater China for informing national disease management and identifying clinical gaps yet to be resolved. Methods A systematic search literature using seven databases (Web of Science, PubMed, Medline, Cochrane Central, China National Knowledge Infrastructure, Wanfang, and Weipu) was performed to identify interventional and observational studies that reported the impact of HCC on cost or QoL and published before April 6, 2021. The focus population included adult patients with HCC in greater China. This review excluded any studies that focused on any specific treatment. Study quality was assessed using the Effective Public Health Practice Project tool. Results Of 39,930 studies retrieved, 27 were deemed eligible for inclusion. The methodologies, perspectives and data sources used in studies were heterogeneous. In greater China, while few studies reported the health expenditures of HCC patients and investigations about economic burden at national level was lacking, the significant economic impact of HCC on patients and their families had been reported. Health-related costs increased as the disease deteriorated. Additionally, HCC also has a negative impact on the QoL of patients, mostly in terms of physical, cognitive, social functioning and severe symptoms. Conclusions HCC has brought significant economic and QoL burden to patients in greater China. Both physical and psychological factors predicted QoL in patients with HCC in greater China. Future studies should explore the disease-related economic effects on Chinese patients and their families, the effects of physical and psychological factors on QoL and the relationships of physical and psychological factors in the region. Systematic Review Registration:www.crd.york.ac.uk/prospero/display_record.php?RecordID=278421, PROSPERO: CRD42021278421